The effects of international theater directing on the trends of the Iraqi director - Jiad, Sahib; Omran, Kazem (Al-Adab Journal, 2022)
The influences of the world theater play depend on the direction of the Iraqi director on a number of determinants in light of the need of the theater and the changing of its data from one form to another. Therefore, these influences followed other forms of life, including the artistic field in general and the theatrical art in particular, which resulted in new developments. From ancient traditional themes to the production of forms and content that did not fill the local recipient, despite the retreat of some of them towards the classical themes or written in the discourse of the world theater, but is not circulation to us, through the components of intellectual and aesthetic new and innovative techniques, (And dialectical) of the social, economic and political realities, within the system of artistic presentation in the styles of directors and their dramatic and directing directions and their diversity, directly influenced by the political variables on the structure of the play and its discourse. Therefore, the research pages included in its methodological framework, especially the problem of research, and its identification of the following question: What are the effects of the world theater production on the direction of the Iraqi director? The importance of the research lies in that it highlights the effects of the world theater experiences on the beginnings of the theater experimental experiences in Iraq and its history and the scandals of its experience. While the objective of research in the detection of the effects of global theater output on the directions of the Iraqi director and determined the data framework theoretical in two sections: The first showed the concept of theatrical output and the experiences of the most important directors in the world This course deals with the transformations of the Iraqi and European directors in their visions and their readings of the social, economic and political events with a direct impact on the general directors and the consequent influences on the theater and the directing system in particular. And in the second section, which deals with and reveals the experiences of Iraqi directors and the effects of the world stage and trends in the stages and stylistic changes in the Iraqi theater. Then comes the study of what resulted from the theoretical framework of the indicators of the theoretical framework of the former, and access to the study of previous studies and their relationship to the title and the study of the current study.